(μ-4-Methyl-benzene-thiol-ato-κS:S)bis-[carbon-yl(η-cyclo-penta-dien-yl)molybdenum(II)] - Wong, R.C.S.; Ooi, M.L.; Ng, S.W. (International Union of Crystallography, 2008)
The asymmetric unit of the title compound, [Mo(2)(C(5)H(5))(2)(C(7)H(7)S)(2)(CO)(2)], consists of two half-mol-ecules, each molecule lying on a centre of symmetry. The thiol-ate groups function as bridges between the Mo(II) atoms, which adopt a quasi-octa-hedral geometry. In the octa-hedral environment the two ligating S atoms are in a cis arrangement.